The role of Gadd45b in neurologic and neuropsychiatric disorders: An overview - Shen, Xiao-yue; Shi, Shu-han; Li, Heng; Wang, Cong-cong; Zhang, Yao; Yu, Hui; Li, Yan-bin; Liu, Bin (Frontiers in Molecular Neuroscience, 2022)
Growth arrest and DNA damage-inducible beta (Gadd45b) is directly intertwined with stress-induced DNA repair, cell cycle arrest, survival, and apoptosis. Previous research on Gadd45b has focused chiefly on non-neuronal cells. Gadd45b is extensively expressed in the nervous system and plays a critical role in epigenetic DNA demethylation, neuroplasticity, and neuroprotection, according to accumulating evidence. This article provided an overview of the preclinical and clinical effects of Gadd45b, as well as its hypothesized mechanisms of action, focusing on major psychosis, depression, autism, stroke, seizure, dementia, Parkinson’s disease, and autoimmune diseases of the nervous system.